2016
DOI: 10.1007/s40618-016-0559-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selenium on short-term control of hyperthyroidism due to Graves’ disease treated with methimazole: results of a randomized clinical trial

Abstract: Our study, carried out in a selenium-sufficient cohort of GD patients, failed to show an adjuvant role of selenium in the short-term control of hyperthyroidism. However, selenium might be beneficial in patients from selenium-deficient areas, as well as in the long-term outcome of antithyroid treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
38
1
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 20 publications
3
38
1
4
Order By: Relevance
“…In another recent randomized clinical trial performed in selenium-sufficient patients, we did not observe a beneficial effect of selenium in patients with Graves hyperthyroidism treated with methimazole, in terms of short-term, prompter control of thyroid hyperfunction [5] . Based on the combined results of these two studies, we believe that selenium supplementation might be offered to patients with Graves hyperthyroidism only if selenium deficiency is documented.…”
contrasting
confidence: 72%
“…In another recent randomized clinical trial performed in selenium-sufficient patients, we did not observe a beneficial effect of selenium in patients with Graves hyperthyroidism treated with methimazole, in terms of short-term, prompter control of thyroid hyperfunction [5] . Based on the combined results of these two studies, we believe that selenium supplementation might be offered to patients with Graves hyperthyroidism only if selenium deficiency is documented.…”
contrasting
confidence: 72%
“…A recently published double-blind, placebo-controlled trial could not provide evidence of an effect of Se supplementation (300 µg/day) on either the response to treatment or the recurrence rate in GD [19]. Similarly, a trial with Se supplementation in an Se-sufficient cohort of patients failed to demonstrate an adjuvant role in the short-term control of hyperthyroidism [20]. On the other hand, two randomized studies, from China [21] and from Sweden [22], reported a faster remission of GD with Se treatment, and the Chinese trial additionally demonstrated a decrease in serum TSH receptor antibody (TRAb) concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…The discrepancy may be explained by the fact that patients in that study had a mild GO [8], whereas the majority of patients in our study had a moderate-to-severe GO, thereby making the 2 populations difficult to compare. In addition, the study by Tanda et al [8] was performed in a secondary referral center, where patients are more likely to receive a prompt treatment for both hyperthyroidism and ophthalmopathy, with anti-thyroid drugs and/or selenium [22][23][24][25], which may result in an overall better GO outcome in the long term and in the prevention of GO deterioration over time. In contrast, our study was performed in a tertiary referral center, where most patients are seen long after the initial diagnosis, and may not have received a prompt initial treatment.…”
Section: Discussionmentioning
confidence: 99%